Sex estimation using measurements of the proximal femur in a historical population from Poland - Wysocka, Joanna; Cieślik, Agata I.; Danel, Dariusz P. (Anthropological Review, 2023)
Sex estimation is one of the most important components in assessing the biological profile of an individual. In an archaeological context, the pelvis, which is the most dimorphic part of the skeleton, is often poorly preserved, which can cause an inability to use morphological sex estimation methods. Therefore, alternative methods are required in such cases. Because the utility of the metric methods based on the femur measurement has been confirmed, and the bone is usually available for examination due to its good preservation, developing methods using the landmarks of the femur could have important implications in sex estimation. This study aimed to derive a discriminant function equation for a Polish archaeological population based on measurements of the proximal end of the femur. The study sample included individuals from a medieval cemetery in Milicz (n = 62) and an early modern necropolis at Czysty Square in Wrocław, Poland (n = 162). The analysis included seven measurements collected from the right and left proximal femora. To estimate the reproducibility of the measurements, intra-and interobserver errors and reliability coefficients were calculated. Subsequently, univariate and stepwise discriminant analyses were performed, and the sex sectioning points and equations were proposed. No differences were observed between measurements of the right and left femora. The results indicated a high utility and reproducibility of the FHD measurement (regardless whether left or right femur was measured). The discriminant equations for sex estimation reached an accuracy of 83.0–92.3%, which implies the utility of the function on Polish historical populations when the other methods for sex estimation cannot be used.